2016
DOI: 10.1186/s13287-016-0418-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of proangiogenic features in mesenchymal stem cells derived from bone marrow, adipose tissue, umbilical cord, and placenta

Abstract: BackgroundMesenchymal stem cells (MSCs) have been widely proven effective for therapeutic angiogenesis in ischemia animal models as well as clinical vascular diseases. Because of the invasive method, limited resources, and aging problems of adult tissue-derived MSCs, more perinatal tissue-derived MSCs have been isolated and studied as promising substitutable MSCs for cell transplantation. However, fewer studies have comparatively studied the angiogenic efficacy of MSCs derived from different tissues sources. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
116
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(127 citation statements)
references
References 50 publications
7
116
1
3
Order By: Relevance
“…MSCs have been widely proven effective for therapeutic angiogenesis in ischemia animal models as well as clinical vascular diseases. However, heterogeneous proangiogenic properties of MSCs derived from different tissue origins have been described and these differences are likely linked to the environment (Du et al 2016b). In this study, we observed an increased expression for angiogenic genes ANG1, ANG2, FLT1 and VEGF in ALDH ?…”
Section: Discussionsupporting
confidence: 48%
“…MSCs have been widely proven effective for therapeutic angiogenesis in ischemia animal models as well as clinical vascular diseases. However, heterogeneous proangiogenic properties of MSCs derived from different tissue origins have been described and these differences are likely linked to the environment (Du et al 2016b). In this study, we observed an increased expression for angiogenic genes ANG1, ANG2, FLT1 and VEGF in ALDH ?…”
Section: Discussionsupporting
confidence: 48%
“…Further our study also revealed that the modulation of secretory profiles translated to enhanced sprouting assessed via rECM gelbased angiogenesis assay. Heterogeneous proangiogenic properties of MSCs as a function of tissue origins have been previously reported (Amable, Teixeira, Carias, Granjeiro, & Borojevic, 2014;Du et al, 2016;Hsieh et al, 2013). Studies have demonstrated that MSCs derived from bone marrow and placental chorionic villi exhibited significant therapeutic angiogenic activities compared with those harvested from adipose tissue or umbilical cord (Du et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Heterogeneous proangiogenic properties of MSCs as a function of tissue origins have been previously reported (Amable, Teixeira, Carias, Granjeiro, & Borojevic, 2014;Du et al, 2016;Hsieh et al, 2013). Studies have demonstrated that MSCs derived from bone marrow and placental chorionic villi exhibited significant therapeutic angiogenic activities compared with those harvested from adipose tissue or umbilical cord (Du et al, 2016). On the other hand, studies have also reported that adipose tissue as well as umbilical cord-derived MSCs exhibit better proangiogenic profile than bone marrow-derived MSCs (Amable et al, 2014;Hsieh et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…For example, Oswald et al differentiated MSCs into ELCs using vascular endothelial growth factor (VEGF), and the ELCs expressed endothelial‐specific markers, kinase insert domain receptor ( KDR ) and von Willebrand factor ( vWF ). In another study by Du et al, human MSCs during endothelial differentiation induced by VEGF showed endothelial cell phenotypes in culture. In addition to soluble growth factors, complete endothelial differentiation of stem cells requires signaling cues from the extracellular matrix (ECM) .…”
Section: Introductionmentioning
confidence: 89%